Staphylococcus aureus Interferes with Streptococci Spatial Distribution and with Protein Expression of Species within a Polymicrobial Oral Biofilm - Etyene Schnurr; Pune N. Paqué; Thomas Attin; Paolo Nanni; Jonas Grossmann; Silva Holtfreter; Barbara M. Bröker; Christian Kohler; Binh An Diep; Apoena de Aguiar Ribeiro; Thomas Thurnheer (MDPI AG, 2021)
We asked whether transient Staphylococcus aureus in the oral environment synergistically interacts with orally associated bacterial species such as Actinomyces oris, Candida albicans, Fusobacterium nucleatum, Streptococcus oralis, Streptococcus mutans, and Veillonella dispar (six-species control biofilm 6S). For this purpose, four modified biofilms with seven species that contain either the wild type strain of the S. aureus genotype (USA300-MRSA WT), its isogenic mutant with MSCRAMM deficiency (USA300-MRSA ΔMSCRAMM), a methicillin-sensitive S. aureus (ST72-MSSA-) or a methicillin-resistant S. aureus (USA800-MRSA) grown on hydroxyapatite disks were examined. Culture analyses, confocal-laser-scanning microscopy and proteome analyses were performed. S. aureus strains affected the amount of supragingival biofilm-associated species differently. The deletion of MSCRAMM genes disrupted the growth of S. aureus and the distribution of S. mutans and S. oralis within the biofilms. In addition, S. aureus caused shifts in the number of detectable proteins of other species in the 6S biofilm. S. aureus (USA300-MRSA WT), aggregated together with early colonizers such as Actinomyces and streptococci, influenced the number of secondary colonizers such as Fusobacterium nucleatum and was involved in structuring the biofilm architecture that triggered the change from a homeostatic biofilm to a dysbiotic biofilm to the development of oral diseases.